THE IMPLEMENTATION OF CUSTOMARY VALUES ON THE ADMINISTRATION OF GOVERNANCE: A STUDY ON THE VILLAGE GOVERNANCE BASED ON LOCAL WISDOM AT NAGARI KAPAU, AGAM REGENCY OF WEST SUMATRA, INDONESIA - Malau H.; Supriyono B.; Hakim A.; Muluk M.R.K. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Changing in governance practices from centralized to decentralize and shifting from uniformity to diversity in village governance do not necessarily mean customary values that are owned and maintained can be used in the administration of customary (adat) village governance. The problem of the customary village governance arises from the uniformity of villages, the lack of recognition of customary values and the number of customary villages that have been declared during the New Order government. However, the issuance of Law No. 6 of 2014 concerning villages at this time is expected that the customary values can be accommodated to strengthen the course of customary village governance. This study aims to describe and analyze the application of traditional values (local wisdom) used in the administration of Nagari Kapau Government. This study used a qualitative approach whose data collection methods were in the form of in-depth interviews, observation and data triangulation that was carried out to increase credibility. The results of the study revealed that the uniformity of villages in the New Order era apparently was not able to eliminate the traditional values that are owned directly; even the traditional values were still maintained and used in the practice of governing the Nagari Kapau government in Agam Regency, West Sumatera Province. The customary values (local wisdom) used in the task of organizing governance will be described as follows (1) the Kalarasan Koto Philiang Chaniago is used in the decision-making process of the Minangkabau indigenous people, (2) the Adat Basandi Syarak, Syarak Basandi Kitabullah (ABSSBK) is used as a philosophy live in the Minangkabau Indigenous people, (3) the Penghulu (Ninik Mamak) is used as the Nagari owner in the Minangkabau indigenous people, (4) Wali Nagari (the Head of the Customary Village) is used as the Head of Government in the Minangkabau Indigenous Community, (5) Harta Pusaka (Sako Pusako) is used as a legacy system in the Minangkabau Indigenous people, (6) Suku is used as a condition for the establishment of Nagari in the Minangkabau Indigenous people, (7) Tungku Tigo Sajarangan (the three Sajarangan Stove) and Tali Tigo Sapilin as a pattern of Leadership in Minangkabau Indigenous people.